FINANCIAL RATIO ANALYSIS IN ASSESSING THE PERFORMANCE OF COMPANY PROFITABILITY AND LIQUIDITY AT PT. PERTAMINAGEOTHERMAL ENERGYTBK PERIOD 2022-2023 - Desi; Putri Sumaiyya; Siti Rahmah; Widia Safitri (PT. Jurnal Center Indonesia Publisher, 2026)
This research was conducted to assess the financial performance of PT Pertamina Geothermal EnergyTbk for the 2022–2023 period using a financial ratio analysis approach focused on profitability and liquidity ratios. The research method used is quantitative descriptive, utilizing secondary data sourced from the company's financial statements. Indicators used in the profitability analysis includeNet Profit Margin, Return on Assets( ROA), and Return on Equity(ROE), while liquidity analysis is carried out usingCurrent Ratio, Quick Ratio, AndNet Working Capital Ratio.The analysis results show an increase in the profitability ratio, reflecting improvements in operational efficiency and the company's ability to utilize assets to generate profits. On the other hand, although the liquidity ratio has improved, its value has not yet reached the ideal level, indicating that the company still faces challenges in meeting its short-term obligations. Overall, PT PertaminaGeothermal EnergyTbk during the 2022–2023 period showed increasingly improving profitability performance, but still needs to pay attention to and strengthen liquidity conditions to maintain the company's financial stability.